Nonreciprocal chromosomal translocations in renal cancer involve multiple DSBs and NHEJ associated with breakpoint inversion but not necessarily with transcription. Issue 4 (23rd January 2013) - Ali, Hanif; Daser, Angelika; Dear, Paul; Wood, Henry; Rabbitts, Pamela; Rabbitts, Terence
Abstract Chromosomal translocations and other abnormalities are central to the initiation of cancer in all cell types. Understanding the mechanism is therefore important to evaluate the evolution of cancer from the cancer initiating events to overt disease. Recent work has concentrated on model systems to develop an understanding of the molecular mechanisms of translocations but naturally occurring events are more ideal case studies since biological selection is absent from model systems. In solid tumours, nonreciprocal translocations are most commonly found, and accordingly we have investigated the recurrent nonreciprocal t(3;5) chromosomal translocations in renal carcinoma to better understand the mechanism of these naturally occurring translocations in cancer. Unexpectedly, the junctions of these translocations can be associated with site‐specific, intrachromosomal inversion involving at least two double strand breaks (DSB) in cis and rejoining by nonhomologous end joining or micro‐homology end joining. However, these translocations are not necessarily associated with transcribed regions questioning accessibility per se in controlling these events. In addition, intrachromosomal deletions also occur. We conclude these naturally occurring, nonreciprocal t(3;5) chromosomal translocations occur after complex and multiple unresolved intrachromosomal DSBs leading to aberrant joining with concurrent interstitial inversion and that clonal selection of cells is the critical element in cancer development emerging from a plethora of DSBs that may not always be pathogenic. © 2013 Wiley Periodicals, Inc.